Probable depression and its correlates among undergraduate students in Johannesburg, South Africa - Croock, Jeremy; Mpinganjira, Mafuno G.; Gathoo, Kaashifa; Bulmer, Robyn; Lautenberg, Shannon; Dlamini, Qhayiyakazi; Londani, Pfanani; Solontsi, Azola; Stevens, Chanel; Francis, Joel M. (Frontiers in Psychiatry, 2023)
Background Depression is associated with high rates of morbidity and mortality. Globally, depression is higher among university students than the general population—making it a significant public health problem. Despite this, there is limited data on the prevalence in university students in the Gauteng province, South Africa. This study determined the prevalence of screening positive for probable depression and its correlates among undergraduate students at the university of the Witwatersrand, Johannesburg, South Africa. Methods A cross-sectional study, using an online survey was conducted among undergraduate students at the University of the Witwatersrand in 2021. Patient Health Questionnaire (PHQ-2) was used to assess the prevalence of probable depression. Descriptive statistics was computed and conducted bivariate and multivariable logistic regression to identify factors associated with probable depression. Age, marital status, substance use (alcohol use, cannabis use, tobacco use, and other substance use) were included in the multivariable model apriori determined confounders and other factors were only added if they had a p-value <0.20 in the bivariate analysis. A p-value of 0.05 was considered statistically significant. Results The response rate was 8.4% (1046/12404). The prevalence of screening positive for probable depression was 48% (439/910). Race, substance use, and socio-economic status were associated with odds of screening positive for probable depression. Specifically reporting white race (adjusted OR (aOR) = 0.64, 95% CI: 0.42, 0.96), no cannabis use (aOR = 0.71, 95% CI: 0.44–0.99), higher spending power in the form of having the most important things but few luxury goods (aOR = 0.50, 95% CI: 0.31, 0.80) and having enough money for luxury goods and extra things (aOR = 0.44, 95% CI: 0.26–0.76) were associated with lower odds of screening positive for probable depression. Discussion: In this study, screening positive for probable depression was common among undergraduate students at the University of the Witwatersrand, Johannesburg, South Africa and associated with sociodemographic and selected behavioral factors. These findings call for strengthening the awareness and use of counselling services among undergraduate students.